2003
DOI: 10.1021/bi034975i
|View full text |Cite
|
Sign up to set email alerts
|

The Functional Significance of the Monomeric and Trimeric States of the Photosystem II Light Harvesting Complexes

Abstract: The main light harvesting complex of photosystem II in plants, LHCII, exists in a trimeric state. To understand the biological significance of trimerization, a comparison has been made been LHCII trimers and LHCII monomers prepared by treatment with phospholipase. The treatment used caused no loss of chlorophyll, but there was a difference in carotenoid composition, together with the previously observed alterations in absorption spectrum. It was found that, when compared to monomers, LHCII trimers showed incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
47
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 57 publications
(115 reference statements)
10
47
0
Order By: Relevance
“…It has long been known, that LHCII fluorescence quenching in vitro, for example upon acidification, has similarities with nonphotochemical quenching of Chl fluorescence observed in entire plants under high-light conditions (27). Also similarly as in plants, the extent of fluorescence quenching in vitro is influenced by the presence of the carotenoid Zea (28). We therefore first determined Coupling Car S1ϪChl for LHCII as a function of different conditions that can lead to fluorescence quenching.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…It has long been known, that LHCII fluorescence quenching in vitro, for example upon acidification, has similarities with nonphotochemical quenching of Chl fluorescence observed in entire plants under high-light conditions (27). Also similarly as in plants, the extent of fluorescence quenching in vitro is influenced by the presence of the carotenoid Zea (28). We therefore first determined Coupling Car S1ϪChl for LHCII as a function of different conditions that can lead to fluorescence quenching.…”
Section: Resultsmentioning
confidence: 98%
“…2B demonstrates the direct, linear correlation between Coupling Car S1ϪChl and fluorescence quenching (NPQ), as quantified in this manner. For LHCII preparations that do not contain Zea significantly less fluorescence quenching can be observed in otherwise identical experimental conditions (28). It is, however, important to note, that Zea is not absolutely mandatory to achieve quenching.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…As the regulated ∆pH-and zeaxanthin-dependent NPQ is believed to occur within the LHCII antenna and depend on its oligomerization state (Horton et al 1996;Wentworth et al, 2004) the strongly reduced abundance of Lhcb proteins in the F2 mutant ( Fig. 1) (Bossmann et al, 1997;Krol et al, 1995Krol et al, , 1999 can easily explain the lower NPQ in the F2 mutant.…”
Section: Discussionmentioning
confidence: 99%
“…The role of pH-and zeaxanthin-dependent shifts in the oligomerization state of LHCII in developing the rapidly relaxing energy dependent component (qE) of NPQ is well established with qE representing the major protective mechanism against photoinhibitory damage of PSII (Horton et al, 1996; Niyogi, 1999). It has been demonstrated that trimers of LHCII exhibit the optimum level of non-photochemical energy dissipation by modulating the development of the quenched state of the complex (Wentworth et al, 2004).…”
Section: Research Articlementioning
confidence: 99%